PENGARUH JUMLAH BARIS TANAMAN JALUR HIJAU JALAN DALAM MEREDUKSI PARTIKEL TIMBAL (PB) DARI EMISI KENDARAAN BERMOTOR (STUDI KASUS JALUR HIJAU ACACIA MANGIUM JALAN TOL JAGORAWI) - Rachmad Hermawan; Cecep Kusmana; Nizar Nasrullah; Lilik Budi Prasetyo (Media Konservasi, 2011)
Structure of roadside vegetation was assumed to have effects in reducing lead concentration in the ambient air.  One of the structure factors was number of rows.  The objectives of the research were: (a) to determine the effects of different number of plant rows in reducing lead concentration; (b) to determine the decreasing pattern of Pb particle concentration in the ambient air surrounding the roadside vegetation. Air sample to analyze the concentration of Pb particles in the ambient air was collected on 4 collection point: point emission (roadside), 5 m, 15 m and 30 m behind the roadside vegetation; air samples was also collected from an openspace plot. The results showed that differences of tree row number affected the decrease of Pb particle concentration; the more the number of tree rows, the greater the decrease of Pb particle concentration. Two plant rows of roadside vegetation had same capability with more two plant rows of roadside vegetation in reducing Pb particle concentration.  There was a trend that the increasing distance of the roadside would decrease the level of Pb concentration.   Keywords: Pb particle, roadside vegetation, plant row